The Rhetoric of the Oppressed Women: The Autobiography of the Iraqi Womanhood A Research in the Mechanisms of the Rhetorical Proceeding in " Alagnabia - The Foreigner" by Alia Mamdouh (Journal of the College of Education for Women, 2019)
phenomenon in the Arab women's contemporary literature, but it is rare in Iraqi women'sliterature and falls short to the level of the phenomenon until now. Perhaps this is one of themain reasons that caused the reluctance of researchers to study it, and this is probably the firstacademic research in this field.This research followed the discourse of Autobiography of women in Iraq, depending on thetwo factors of charter and reference of the elements of Philippe Lejeune’s definition of thegenre of Autobiography, without focusing on narrative method, so it handled notes,memories, diaries and biography of the other and counted all under the genre of theBiography.It came in three sections, the first followed: The tracks of development of theBiography of Iraqi womanhood from its inception, and then it followed the kinetics ofdevelopment from self-dissolved in community affairs and public to the self that is candidateto biography of others down to the independent self.The second topic addressed: the definition of the term of Rhetoric of the oppressedpeople by Jabir Usfour, and suggested the term (The Rhetoric of the Oppressed women),explaining the elements that allowed classification of Iraqi women Biographies in itsframework. The research also explained the legality of the study of Biography on the basis ofthe sayings of old Arab rhetoric researcher in advantage of Mohammed Omari in the rhetoricof the Biography.In the third section the research singled the auto biography of the Iraqi writer AliaMamdouh in her book "The Foreigner" issued in 2013, as one of the most prominentindependent model of Biography in a literary form. It also approached the main rhetoricalmechanisms followed by the text- focusing on the rhetoric of textual seuiles in the headline,the sub-titles and at the preface – Moreover, it focused on techniques that came on the basis ofreading the text and ranking it within the rhetoric of repression, through studying the rhetoricof fear - that was represented in the genre of the discourse and in the setting up of thediscourse - and the rhetoric of silence - represented in the implicitating and the delet ofFocalisation.